2030 AGENDA AND SUSTAINABLE MIGRATION GOVERNANCE: A COMPARISON BETWEEN EUROPEAN UNION AND BRAZILIAN CONTEXTS - Guerra, Sidney; Chaloub, Luisa (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2024)
The main focus of this paper is to analyse and compare the European Union and Brazilian current migration contexts, through the 2030 Agenda and sustainable migration governance framework. Other than that, it tries to understand, throughout a historical and contextual reconstruction, how the sharing of best practices between those two actors could collaborate in the construction of migration governance that would lead to a reasoning which will substantiate effective legislation and politics in this matter. In this scenario, the contextualist-historical method is adopted, as it is the most suitable and reliable for understanding and better assessing the topic, in order the anticipate the epistemological issues that could arise from this work. Besides that, an interdisciplinary comparative analysis is also necessary. This paper outlines an unprecedented and necessary strategy for addressing this subject in order to fill the existing literature gap in the field, both in terms of topic and methodology. After a brief overview of the proposed topics, it concludes that although it is not possible to speak of joy or celebration in the context of migration governance, which involves so many still suffering and being forced to leave their homes due to individual persecutions, conflicts, or many other reasons, whether in Europe or South America without. The response given in Brazil, to the large flux of migration which the country received in the last years, feeds the hope that it is possible to welcome these people with more dignity and humanity, serving as an example to the rest of the world.